Homocysteine and ischaemic stroke in men: the Caerphilly study - Fallon, U (BMJ Group, 2001)
OBJECTIVE—To assess the risk of ischaemic stroke associated with total serum homocyst(e)ine (tHcy) concentration. DESIGN—Cohort study. SETTING—Caerphilly, South Wales PARTICIPANTS—2254 men age 50 to 64 years recruited between 1984 and 1988. RESULTS—107 men developed ischaemic stroke and mean follow up time was 10.2 years. There was no significant difference in mean serum total homocyst(e)ine levels between stroke cases (12.2 µmol 95% CI 11.6 to 13.1) and non-cases (11.7 µmol 95% CI 11.5 to 11.9) (p=0.14). There was no significant risk for a standard deviation increase in homocyst(e)ine (adjusted hazard ratio = 1.1, 95% CI 0.9 to 1.4). An interaction was observed between homocyst(e)ine and age at entry (p=0.003). The adjusted odds ratio comparing the top quintile of homocyst(e)ine with the rest was 2.5 (95% CI 1.0 to 6.2) for strokes occurring under 65 years and 0.5 (95% CI 0.2 to 1.3) at 65 years or older (p value for interaction =0.02). Risk also differed by blood pressure status. The adjusted hazard ratio for a standard deviation increase in homocyst(e)ine was 0.8, (95% CI 0.6 to 1.2) for normotensive men and 1.3 (95% CI 1.1 to 1.7) for hypertensive men (p value for interaction =0.01). CONCLUSIONS—Overall, there is no significant relation between homocyst(e)ine and ischaemic stroke in this cohort. However, its aetiological importance may be greater for premature ischaemic strokes (<65 years) and in hypertensive men.   Keywords: homocyst(e)ine; ischaemic stroke; cohort